2017
DOI: 10.1016/j.ntt.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Isoflurane exposure leads to apoptosis of neurons and oligodendrocytes in 20- and 40-day old rhesus macaques

Abstract: Previously we reported that a 5-hour exposure of 6-day-old (P6) rhesus macaques to isoflurane triggers robust neuron and oligodendrocyte apoptosis. In an attempt to further describe the window of vulnerability to anesthetic neurotoxicity, we exposed P20 and P40 rhesusmacaques to 5 h of isoflurane anesthesia or no exposure (control animals). Brains were collected 3 h later and examined immunohistochemically to analyze neuronal and glial apoptosis. Brains exposed to isoflurane displayed neuron and oligodendrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 22 publications
3
72
0
Order By: Relevance
“…Our findings do not elucidate the possible mechanisms of long-term effects of repeated anaesthesia exposure in infancy. However, recent reports confirm that early anaesthesia exposure results in neuro-and glio-apoptosis, whether that exposure occurs on postnatal day 6, 34e36 20, or 40 in infant rhesus monkeys exposed to isoflurane, 11,37 which were the ages of repeated exposure in the present study. Loss of neurones and oligodendrocytes was observed in amygdala and hippocampus, 37 structures involved in the development of emotional behaviour.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our findings do not elucidate the possible mechanisms of long-term effects of repeated anaesthesia exposure in infancy. However, recent reports confirm that early anaesthesia exposure results in neuro-and glio-apoptosis, whether that exposure occurs on postnatal day 6, 34e36 20, or 40 in infant rhesus monkeys exposed to isoflurane, 11,37 which were the ages of repeated exposure in the present study. Loss of neurones and oligodendrocytes was observed in amygdala and hippocampus, 37 structures involved in the development of emotional behaviour.…”
Section: Discussionsupporting
confidence: 68%
“…However, recent reports confirm that early anaesthesia exposure results in neuro-and glio-apoptosis, whether that exposure occurs on postnatal day 6, 34e36 20, or 40 in infant rhesus monkeys exposed to isoflurane, 11,37 which were the ages of repeated exposure in the present study. Loss of neurones and oligodendrocytes was observed in amygdala and hippocampus, 37 structures involved in the development of emotional behaviour. Early loss of neurones and oligodendrocytes could alter the developmental trajectory of the central nervous system in a number of ways, as early lesions have different consequences to lesions later in life as their effects interact with the developmental trajectory of cognitive and emotional processes.…”
Section: Discussionsupporting
confidence: 68%
“…Regardless of the species or animal model used, general anesthetics like ketamine administered during sensitive periods of development at anesthetic and sub‐anesthetic doses have deleterious effects on the developing brain (Brambrink et al, ; Creeley et al, ; Olutoye et al, ; Rizzi, Carter, Ori, & Jevtovic‐Todorovic, ; Rizzi, Ori, & Jevtovic‐Todorovic, ; Slikker et al, ; Walters & Paule, ). The exact period of development during which a rhesus macaque's brain is sensitive to the effects of ketamine is still unclear (Schenning et al, ). For rodents, it is apparent that this period spans the first postnatal weeks.…”
Section: Discussionmentioning
confidence: 99%
“…For rodents, it is apparent that this period spans the first postnatal weeks. In monkeys, some evidence has shown the period of sensitivity to neuronal cell death induced by general anesthesia, including ketamine, extends to postnatal day (PND) 7 (Walters & Paule, ), while another study suggests that the developing brain is sensitive to isoflurane up to postnatal day 40 (Schenning et al, ). We found that performance on the preferential looking task was impaired in most animals that received a single sedative dose prenatally, though we acknowledge that some cell sizes were small.…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerability to anesthesia-associated cell death is confined to a temporal window coincident with high levels of brain growth and synaptogenesis (2). Human correlates of these processes suggest that vulnerability to injury for pediatric patients receiving anesthesia may extend into early childhood (3,4). Neuronal injury by volatile anesthetics may be responsible for lasting behavioral and learning deficits in children exposed to the perioperative environment (5).…”
Section: Introductionmentioning
confidence: 99%